Exertional rhabdomyolysis - Brown, T. P. (The Physician and Sportsmedicine, 2004)
Exertional rhabdomyolysis is an uncommon diagnosis, but because its complications can be severe, clinicians need a thorough understanding of this syndrome. When skeletal muscle cell membranes are damaged, their intracellular contents enter the bloodstream and can cause potentially serious sequelae, even death. Intense exercise, some viral infections, and certain genetic disorders increase the risk. Serum creatine kinase levels are the diagnostic gold standard. The treatment of rhabdomyolysis consists of early detection, therapy for the underlying cause, measures to prevent renal failure, and correction of metabolic complications.